The Legal Position of Elopement Marriage (sirī) Against Positive Law After the Decision of the Constitutional Court Number 46/PUU-VIII/2010 - Edwin Yulanda; Nazaruddin; Sapriadi; Noercholis Rafid (Fakultas Syariah Institut Agama Islam Negeri Palu, 2024)
The purpose of this study is to examine the legal application of elopement marriage (sirī) after the Constitutional Court Decision Number 46/PUU-VIII/2010. This research is a qualitative research and the type of research is library research. The data collection method used is literature study. The results showed that; the legal application of elopement marriage (sirī) after the decision of the Constitutional Court Number 46/PUU-VII/2010 has been regulated in Government Regulation of the Republic of Indonesia Number 9 of 1975. This is a positive law that must be followed by all Indonesian citizens. The application of this law is in line with religious values in the context of the Indonesian nation, in accordance with the Pancasila. The impact of this decision also changes people's attitudes towards siri marriage because children born from elopement marriage (sirī) still have a right recognized by the state. The message conveyed in this decision encourages people to understand the importance of legal recognition and marriage registration to protect the rights of children born from elopement marriage (sirī).